2005
DOI: 10.1097/00001888-200502000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Systems-Based Practice to Residents by Using Independent Study Projects

Abstract: The changing health care marketplace requires new graduates to be familiar with complex health systems. Since 1999 the Oregon Health & Science University internal medicine residency program has offered a seminar-based health systems curriculum, but residents lacked an opportunity to actively apply learned concepts. To achieve this goal, the authors developed a second curricular component, the Health Systems Independent Study Project (HSISP). The HSISP is a self-directed assessment of a health care system or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Additional QI education initiatives have been reported in internal medicine and surgery residency programs (Allen et al 2005;Canal et al 2007;Wong et al 2008). In an attempt to reflect future professional practices, programs have piloted interdisciplinary QI curricula that offer a solution to bridging the QI training gaps between various disciplines (Singh et al 2005;Varkey et al 2006).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Additional QI education initiatives have been reported in internal medicine and surgery residency programs (Allen et al 2005;Canal et al 2007;Wong et al 2008). In an attempt to reflect future professional practices, programs have piloted interdisciplinary QI curricula that offer a solution to bridging the QI training gaps between various disciplines (Singh et al 2005;Varkey et al 2006).…”
Section: Practice Pointsmentioning
confidence: 99%
“…3,5-10 Some published curricula involve seminar and lecture formats that are typically evaluated using pre-and posttests of knowledge. 5,7,8,10 Other curricula incorporate independent-study QI proposals and/or QI projects.…”
Section: Introductionmentioning
confidence: 99%
“…We searched the literature for examples of health systems and QI curricula and their assessment. 3,[5][6][7][8][9][10] Some published curricula involve seminar and lecture formats that are typically evaluated using pre-and posttests of knowledge. 5,7,8,10 Other curricula incorporate independent-study QI proposals and/or QI projects.…”
Section: Introductionmentioning
confidence: 99%
“…17 Though several residency training programs describe using a project-based approach to teach SBP principles [18][19][20] or evaluate quality improvement proposals, 21 none have described the use of rubrics to evaluate residents' writing and thinking skills in their approach to solving SBP problems. Previously published evaluation methods to assess resident competency in SBP included surveys and questionnaires of self-reported improvement, 22 observation using objective structured clinical examination, 23,24 simulated cases with examinations, 25 Web-based tools, 26-28 and simulation.…”
Section: Commentmentioning
confidence: 99%
“…Despite these limitations, our approach mitigates some challenges described when using independent study projects to teach SBP. For example, Allen et al 19 reported that residents tend to select traditional scientific topics for investigation over SBP projects, had difficulty selecting projects or topics, and had problems identifying and arranging meetings with stakeholders.…”
mentioning
confidence: 99%